Rancang Bangun Website Perpustakaan Digital Bagi Mahasiswa Dengan Fitur Peminjaman Online dan Reservasi Buku Otomatis - Devi, Ni Kadek Ari Kesuma; Darmayuda, I Made Raynaldo; Sanjaya, I Nyoman Cakra; Mahardika, I Kadek Riska; Putra, I Made Dea Herdiana Sartian; Linganata, I Made Aril; Sanjaya, I Gede Wahyu (Journal Informatics Nivedita, 2025)
The digital transformation of library services plays a crucial role in improving the accessibility and efficiency of academic information systems. This study aims to design and develop a web-based digital library system equipped with online book lending and automatic reservation features. The system was developed using the Waterfall model, which consists of requirement analysis, system design, software development, testing, and evaluation. Technologies used include PHP, HTML, CSS, JavaScript, and MySQL as the database. The test results indicate that all system features work effectively and receive positive responses from users, especially in terms of accessibility, service speed, and interface usability. The system enables users to access the book catalog online, borrow books without physically visiting the library, and automatically reserve books when the desired book is unavailable. The implementation of this system has been proven to reduce queues, minimize manual errors, and improve the efficiency of library services. This study contributes to digital library transformation and can serve as a reference for similar system development in educational institutions.